Limiting Blood Loss in Orthopaedic Trauma: Strategies and Effects. (May 2020) - Leighton, Jennifer L.; You, Daniel; Schneider, Prism
Highlights: The Acute Coagulopathy of Trauma Shock (ACoTS) has been identified as a specific variant of hemorrhagic shock acting in combination with severe tissue injury. Its presence on arrival in the emergency department may be associated with up to four times the mortality typically seen in more classic hemorrhagic shock patterns. Well-designed trauma-response systems have demonstrated improved outcomes across multiple studies in several countries, with the reduction in preventable deaths cited to be as high as 50%. A special population to consider when designing trauma systems and their protocols is the geriatric population, which is generally defined as greater than 65 years of age, as these patients require lower thresholds for trauma system activation. Tranexamic acid has multiple studies demonstrating its ability to decrease hemorrhage and transfusion requirements with an excellent safety profile Thromboelastography utilizes a surprisingly simple mechanism to deliver a detailed profile of a patient's coagulation state - testing the viscoelastic properties of a blood sample as it progresses through the clotting stages of clot initiation, clot propagation, and clot lysis. It is a promising tool in the realm of targeted resuscitation of polytrauma patients at all points in care. Abstract: Trauma is a major cause of mortality globally, with post-traumatic hemorrhage being the leading cause of death amongst trauma patients. In this paper, the authors review the underlying pathophysiology of trauma-related hemorrhagic shock, specifically the factors which contribute to the development of the acute coagulopathy of trauma shock (ACoTS). We then review the best available evidence for treatment strategies in the pre-hospital setting, as well as the in-hospital setting. Interventions that are strongly supported in the literature include utilization of a well-organized trauma system with direct transport to a designated trauma centre, the early use of tranexamic acid, and damage control orthopaedic surgical techniques and resuscitation protocols. Targeted resuscitation is an evolving field, with use of thromboelastography to guide resuscitation being a particularly promising area. Special trauma populations at particularly high risk are also reviewed, including the geriatric population, as well as unstable pelvic fractures, which are each at increased risk for poor outcomes, and deserve special attention. Major advances have been made in this important area, and ongoing research into the understanding and correction of ACoTS will continue to guide practice.